Monitoring the crystallization of starch and lipid components of the cake crumb during staling. (20th November 2015) - Hesso, N.; Le-Bail, A.; Loisel, C.; Chevallier, S.; Pontoire, B.; Queveau, D.; Le-Bail, P.
Highlights: Fat crystals reorganization was shown by heating cell XRD on non-hydrated stale cake. Amylopectin retrogradation was brought to the fore by heating cell XRD on hydrated stale cake. Amylose retrogradation was highlighted by DSC study at 20 °C. Staling phenomena were more significant at 20 °C than at 4 °C storage temperature. Abstract: Cake staling is a complex problem which has still not been fully understood. Starch polymers retrogradation, which is linked to biopolymers recrystallisation, is the most important factor affecting cake firmness in addition to water migration and fat crystallization. In this study, the effect of storage temperatures of 4 °C and 20 °C on starch retrogradation and fat recrystallization was investigated. Starch retrogradation can be tracked through changes in crystalline structure via X-rays diffraction as well as through melting of crystals via calorimetry. These techniques have been coupled to study the different phenomena occurring during staling. The results revealed that the storage of cakes at 20 °C for 25 days showed more starch polymer retrogradation and more intense fat recrystallization in the β form than at 4 °C. Consequently, the staling was delayed when a low storage temperature like 4 °C was used, which is recommended to retain high quality cakes during storage.